B.S Education System - From Implementation to Possibilities - Ahmed, Sadheer; Islam, Muneer ul; Arshad, Muhammad (Makhz (Research Journal), 2022)
The article under study deals with the BS education system prevailing in Pakistan since 2010. The system has been analyzed to find its strengths and weaknesses. Its major objectives; plan of action; and hurdles in implementation have been highlighted in the paper. The BS system has changed the Pakistan’s higher education system by maximizing student’s involvement in the teaching-learning activities. BS has introduced a paradigm shift which is leading towards practical training and preparing students for the job market. Rote memorization has been discouraged in the system. The evaluation system has been strengthened by replacing the single annual examination system with multi-stage evaluation i.e. awarding credit to sessional work, mid-term and terminal examination.